Intergroup Contact Attitudes Across Peer Networks in School: Selection, Influence, and Implications for Cross‐Group Friendships. Issue 6 (22nd May 2018) - Rivas‐Drake, Deborah; Saleem, Muniba; Schaefer, David R.; Medina, Michael; Jagers, Robert
Abstract : This study offers new insights into the power of peer networks for shaping intergroup relations in a diverse school. Data were drawn from a longitudinal study of sixth–eighth graders ( N = 524; M ageT1 = 11.87; 48% girls; 9% Asian American/Pacific Islander, 28% African American, 13% Latino, 1% Native American, 31% White, 5% Other, and 11% Multiracial) in the Midwestern United States. Students with more positive intergroup contact attitudes (ICA) were most likely to be friends with similarly minded students. Students with more positive ICA were less likely to select friends of the same race/ethnicity than those with less positive ICA. Finally, students' ICA became more similar to their friends' ICA over time. Results implicate school‐level norms and contagion in students' ICA.